2020
DOI: 10.1155/2020/8896601
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Evidence-Based Online Concussion Education to Medical and Healthcare Professionals: The Concussion Awareness Training Tool (CATT)

Abstract: Background. Medical and healthcare professionals report an important gap in their training and knowledge on concussion diagnosis and management. The Concussion Awareness Training Tool (CATT) for medical professionals provides evidenced-based training and resources, representing an important effort to fill this gap. The goal of the current article was to summarize and describe the general uptake of the 2018 relaunch of the CATT for medical professionals and to present results of a quality assurance/quality impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A growing number of patients are now seeking concussion care, as concussion continues to gain recognition as an important public health issue [ 16 ]; however, medical professionals have noted a lack of resources for optimal concussion management [ 6 , 17 ]. Given that optimal concussion management can have a significant impact on a patient’s quality of life, accurate and up-to-date concussion training and resources are essential for all medical professionals, and for family medicine physicians/general practitioners in particular [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of patients are now seeking concussion care, as concussion continues to gain recognition as an important public health issue [ 16 ]; however, medical professionals have noted a lack of resources for optimal concussion management [ 6 , 17 ]. Given that optimal concussion management can have a significant impact on a patient’s quality of life, accurate and up-to-date concussion training and resources are essential for all medical professionals, and for family medicine physicians/general practitioners in particular [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 pre/post-intervention evaluation found a statistically significant positive change in physician practices following completion of the CATT (p < 0.01) [ 5 ]. A more recent quality assessment/quality improvement study of the CATT found that the majority of physician respondents reported the following benefits from using the tool: learning new information (85%), changing the way they diagnose, treat or manage concussion (73%); and recommending CATT to colleagues (71%) [ 6 ]. The tool consists of eight online concussion education modules, each tailored to a specific audience.…”
mentioning
confidence: 99%
“…The CATT has been shown to be effective in significantly raising knowledge of concussion in healthcare professionals, and increasing their confidence in making informed decisions about the appropriate steps to take after a concussion has occurred. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The CATT has been shown to be effective in significantly raising knowledge of concussion in healthcare professionals, and increasing their confidence in making informed decisions about the appropriate steps to take after a concussion has occurred. 16 The CATT-WSW (https://cattonline.com/womens-support-workers/) was developed to "provide women's support workers with the information they need to take an evidencebased approach in responding to and managing concussion" using evidence-based research on IPV-caused BIs. Because the CATT-WSW focuses on IPV, it was the first CATT module to incorporate strangulation, which is highly prevalent in IPV, and can lead to anoxic/hypoxic/ischemic BI, as well as having high levels of lethality.…”
Section: Introductionmentioning
confidence: 99%
“…These include, among others, the institution of the B.C. Injury Research and Prevention Unit (BCIRPU), the development of the Canadian Falls Prevention Curriculum [9], Preventable [10][11][12], Road Safety Strategy 2015 and Beyond [13], Concussion Awareness Training Tool (CATT) [14,15], and Active & Safe Central [16]. One of the essential components required for successful and sustainable implementation of public health interventions includes the communication of accurate, timely, and concise information to decision-makers and other key stakeholders [17].…”
Section: Introductionmentioning
confidence: 99%